2016
DOI: 10.4336/2016.pfb.36.86.990
|View full text |Cite
|
Sign up to set email alerts
|

Hidrogel, calagem e adubação no desenvolvimento inicial, sobrevivência e composição nutricional de plantas híbridas de eucalipto

Abstract: Com a premissa de que a utilização de hidrogel associado à calagem e adubação em plantios de eucalipto aumenta a retenção de água e o teor de nutrientes no solo, objetivou-se avaliar a sobrevivência e o desenvolvimento inicial de clones híbridos de Eucalyptus grandis x Eucalyptus camaldulensis, em função da utilização de hidrogel, calagem e adubação. Em um Argissolo Vermelho, foram dispostos os tratamentos: 1) controle, 2) hidrogel, 3) adubação convencional, 4) adubação + calagem, 5) adubação + hidrogel e 6) a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 8 publications
0
2
0
Order By: Relevance
“…It has been shown that the use of water-retaining polymers (hydrogels) contributes to the retention of water in the soil, making it available to plants in dry periods (Felippe et al, 2016;Silva et al, 2019), as well as improving aeration and the cation exchange capacity, and reducing nutrient leaching (Bartieres et al, 2016;Konzen et al, 2017). However, information on the ecophysiology of fruit tree species in the seedling phase associated with the use of hydrogels is scarce.…”
Section: Introductionmentioning
confidence: 99%
“…It has been shown that the use of water-retaining polymers (hydrogels) contributes to the retention of water in the soil, making it available to plants in dry periods (Felippe et al, 2016;Silva et al, 2019), as well as improving aeration and the cation exchange capacity, and reducing nutrient leaching (Bartieres et al, 2016;Konzen et al, 2017). However, information on the ecophysiology of fruit tree species in the seedling phase associated with the use of hydrogels is scarce.…”
Section: Introductionmentioning
confidence: 99%
“…Likewise, Buzetto et al (2002) and Navroski et al (2014), also verified this positive effect of hydrogel in post-planting of Eucalyptus dunnii. According to Bartieres et al (2016), the use of the hydrogel alone does not favor the growth of the plants, however it increases the survival when compared to the control treatment, without hydrogel or additional fertilization. These results differed from those of Saad et al (2009), in which the use of hydrogel did not result in increased plant survival in both sandy and sandy soils.…”
Section: Discussionmentioning
confidence: 99%
“…The use of hydrogel has been widely spread among forest plantings, as an alternative to overcome severe drought episodes driven by climate change in the tropics (Saha et al 2020). Higher survival rates and satisfactory development have been achieved when using hydrogel in commercial plantings, especially for the Eucalyptus and Pinus species (Bartieres et al, 2016;Mudhanganyi et al,. 2018;Felippe et al,.…”
Section: Introductionmentioning
confidence: 99%